A NEW PARADIGM OF 'SELLING' FOR COMMUNITIES IN THE TRADITIONAL VILLAGE ENVIRONMENT, BEWARE OF ONLINE TRANSACTION FRAUD USING DIGITAL PAYMENT - Fina Carla Rettobjaan, Vitalia; Bagus Aristayudha, AA Ngurah; Widnyani, Ni Made; Putu Krisna Juliharta, I Gede; Ning Septyarini Putri Astawa, Ni Luh Putu (LPPM Univ. Ibn Khaldun Bogor, 2023)
The rapid development of the internet from year to year has encouraged the advancement of information exchange in this world. This also greatly affects the increase in internet use for business transactions both digitally and conventionally to make payment methods using digital payments. Easy and efficient payment methods are certainly inseparable from increasingly sophisticated crimes as well. The implementation of this community service aims to remind the business community to be more vigilant, especially against all attempts of criminal behavior in the transaction process. This activity was attended by 150 people from the Sibang Kaja Traditional Village, both online and offline. The activity lasted for 4 hours which began with the resource person delivering material then continued with the Digital Ethic and Digital Safety applications. After the material presentation session, it was continued with a discussion where the enthusiasm of the participants was seen regarding digital payments. Community service like this should be carried out continuously to increase public awareness in the midst of rampant digital crime.